Encrypting Colored Images Using DNA Sequence Indexing - ابو قاسم كندة; سلمان تيسير (Latakia University Journal -Engineering Sciences Series, 2021)
Many studies adopted different techniques to encrypt color images. This study will focus on using DNA sequences as encryption keys and for the purpose of indexing which will be used to change image elements positions for image encryption. At first HASH string is taken for the image file, the resulted HASH string is converted into DNA. The purpose of taking the hash function of the image file is to obtain a high key sensitivity. The image file is converted to binary format and then encoded with DNA codes. Encrypting of the file with the key through XOR process. After obtaining the encoded file, and pixel locations for the images by making use of three DNA sequences for the image files. Image encryption was evaluated by several factors such as the correlation between adjacent and entropy pixels, image layout, and resistance to differential attacks. It was shown that random DNA sequences could be used as encryption keys and for indexing purposes when encrypting colored images by the obtained results of the evaluation factors